PENDAMPINGAN PASTORAL BAGI ANAK TUNANETRA DI YAYASAN BHAKTI LUHUR MALANG - Maria Vianti Desa (Jurnal Pelayanan Pastoral, 2021)
Every human being has different problems in his life, both problems with himself and his environment. Life problems and destructive problems are very varied, for example; heart, disappointment, depression, emotional wounds, and physical conditions that experience obstacles. This situation is very much needed by pastoral companions to help others in overcoming real problems The assistance given pays attention to several aspects, namely physical, mental, social and spiritual. In pastoral care must meet the spiritual needs of blind children. This study aims to see the implementation, inhibiting factors and support for the pastoral assistance of blind children at the Bhakti Luhur Malang Foundation. The research was conducted at the Bhakti Luhur Foundation guest houses, using a descriptive qualitative approach through the method (Case Study). The results of the research are based on interviews regarding the implementation of pastoral assistance for blind children at the Bhakti Luhur Foundation, according to the person in charge of the guesthouse, in general, it has been carried out according to schedule, sometimes it is not carried out due to other tasks. According to the nurse, sometimes it is done, sometimes it is not because the nurse does not understand mentoring children with visual impairment. The sisters said, still carrying out the ups and downs, asked the expert team. Inhibiting factors according to the person in charge and the nurse; laziness, new tasks happening at the same time. According to the ALMA Sisters, the inhibiting factor; the condition of blind children is very severe. Supporting factors; the person in charge, the ALMA Sisters and the nurses have the same answer; availability of facilities and infrastructure, following technological developments. Thus the research results show that the implementation of mentoring at the Bhakti Luhur Foundation has been carried out according to schedule, but sometimes it is not optimal, it needs to be considered by stakeholders.